IMPROVING LITERACY (READING) SKILLS THROUGH THE USE OF PICTURE STORY BOOKS IN KINDERGARTEN - Ariyani Mela (Journal of Teaching and Education, 2025)
This study aims to improve literacy (reading) skills of early childhood through the use of picture story books in ABA Jragan Kindergarten, Bantul, Yogyakarta. This type of research is Classroom Action Research (CAR) which is carried out in two cycles with the stages of planning, action, observation, and reflection. The research subjects consisted of 11 children in group B (7 boys and 4 girls) aged 5–6 years. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the use of picture story books can improve children's literacy skills, as indicated by an increase in the 'very well developed' category from 36% in cycle I to 64% in cycle II. Picture story books media help children understand the content of the reading, actively ask questions, and are able to retell the content of the story. Thus, the use of picture story books is proven effective in increasing reading interest and literacy skills of early childhood.